Correlation between the antioxidant, total flavonoid and total phenolic content of phaleria macrocarpa fruit extract - Lim, Yee Peng; Pang, Sook Fun; M. M., Yusoff; Jolius, Gimbun (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The effect of temperature and extraction time on the yield of polyphenol and antioxidant activity (DPPH-RSA) of Phaleria macrocarpa fruits was studied. The extraction of polyphenols from Phaleria macrocarpa fruit was performed using a maceration technique. The (TFC) Total Flavonoid Content and Total Phenolic Content (TPC) in the sample was analysed using aluminium chloride colorimetric assay and Singleton’s method, respectively. Meanwhile, the antioxidant activity was determined via DPPH assay. The optimum extraction condition was achieved at 80 ºC and 60 min which yielded 69.5 mg QE/g DW, 183.2 mg GA/g DW and 171.8 mg BHA/g DW, respectively. Pearson correlation coefficient analysis shows excellent correlation coefficient with R2 > 0.91 between the TPC, TFC and antioxidant activities. The method outlined here may serve as a guide to optimize the polyphenol extraction from Phaleria macrocarpa fruit